A rare earth modified high-strength porcelain insulator and a preparation method thereof

CN123017650APending Publication Date: 2026-10-30PINGXIANG HUATONG ELECTRIC PORCELAIN MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611112864.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

刚玉颗粒的强化作用因此不能得到稳定发挥,瓷体的强度也容易出现波动

Benefits of technology

[0017]本发明在刚玉骨架颗粒与铝硅酸盐连续基体之间设置含钇富铝内侧反应区和含铝硅晶体外侧反应区。含钇富铝内侧反应区位于刚玉骨架颗粒表面,含铝硅晶体外侧反应区位于含钇富铝内侧反应区与连续基体之间,使刚玉骨架颗粒与连续基体之间形成逐步过渡。该结构能够减少刚玉骨架颗粒边缘的局部孔隙和组成突变,缓和烧成冷却后形成的局部应力。瓷体受力时,刚玉骨架颗粒能够分担载荷,颗粒外围的反应区能够使裂纹发生偏转或者分叉,从而改善瓷体的结合状态、机械强度和温度变化后的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017650A_ABST
    Figure CN123017650A_ABST
Patent Text Reader

Abstract

The application discloses a rare earth modified high-strength porcelain insulator and a preparation method thereof, and relates to high-aluminum ceramic material, electric ceramic and special ceramic product manufacturing technology. The porcelain insulator comprises an aluminate silicate continuous matrix and corundum skeleton particles dispersed in the aluminate silicate continuous matrix, at least part of the corundum skeleton particles and the aluminate silate continuous matrix form a rare earth modified reaction transition structure, and the rare earth modified reaction transition structure comprises a yttrium-containing aluminum-rich inner reaction zone and an outer reaction zone rich in secondary mullite along the corundum skeleton particles to the aluminate silicate continuous matrix. The preparation method comprises the following steps: double-layer coating of the corundum skeleton particles, pre-fixing treatment, single wet ball milling of the main body porcelain material, low-shear mixing of the double-layer coated corundum skeleton particles, shaping and stage sintering. The application improves the bonding state between the corundum skeleton particles and the aluminate silicate continuous matrix by directional regulation of the interface structure of the corundum particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the manufacturing technology of high-alumina ceramic materials, electrical ceramics and special ceramic products, specifically to a rare earth modified high-strength porcelain insulator and its preparation method. Background Technology

[0002] Porcelain insulators typically use aluminosilicate materials as the ceramic matrix. To improve the mechanical strength of the ceramic body, alumina, calcined bauxite, or corundum particles can be added to the ceramic material. Corundum particles have high hardness and strength, enabling them to play a load-bearing role within the ceramic body.

[0003] However, the composition and structure of corundum particles differ from those of the surrounding aluminosilicate matrix. After firing and cooling, localized porosity, glassy phase segregation, or stress concentration can easily occur at the edges of the corundum particles. When the porcelain insulator is subjected to mechanical loads or temperature changes, cracks may originate from these locations and continue to propagate along the particle edges. Consequently, the strengthening effect of the corundum particles cannot be stably maintained, and the strength of the porcelain body is prone to fluctuations.

[0004] Therefore, it is necessary to improve the interface structure between corundum particles and the aluminosilicate matrix to create a smoother transition between the two, thereby reducing porosity and stress concentration at the particle edges. Summary of the Invention

[0005] The purpose of this invention is to provide a rare earth modified high-strength ceramic insulator and its preparation method, which improves the bonding state between corundum skeleton particles and aluminosilicate continuous matrix, reduces local porosity and stress concentration at the edges of corundum skeleton particles, and enables corundum skeleton particles to stably play a role in bearing load and preventing crack propagation in the ceramic body.

[0006] The above-mentioned technical objective of the present invention is achieved through the following technical solution: a rare earth modified high-strength porcelain insulator, the porcelain insulator comprising a porcelain body, wherein the sintered porcelain body comprises an aluminosilicate continuous matrix and corundum skeleton particles dispersed in the aluminosilicate continuous matrix. At least some of the corundum framework particles and the aluminosilicate continuous matrix form a rare earth modified reaction transition structure; Along the direction of the corundum skeleton particles toward the aluminosilicate continuous matrix, the rare earth modified reaction transition structure sequentially includes an inner reaction zone containing yttrium-rich aluminum and an outer reaction zone containing aluminum-silicon crystals. The yttrium-rich aluminum inner reaction zone is adjacent to the corundum skeleton particles. The yttrium-rich aluminum inner reaction zone contains yttrium and aluminum, and the yttrium content in the yttrium-rich aluminum inner reaction zone is higher than the yttrium content in the aluminosilicate continuous matrix. The outer reaction zone of the aluminum-containing silicon crystal is located between the yttrium-rich aluminum inner reaction zone and the continuous aluminum silicate matrix, and aluminum-containing silicon crystals are distributed in the outer reaction zone of the aluminum-containing silicon crystal.

[0007] Furthermore, the corundum framework particles have α-Al2O3 as the main crystalline phase, and the Al2O3 content of the corundum framework particles is not less than 90%. The corundum skeleton particles are one or more of the following: fused corundum particles, sintered corundum particles, calcined alumina particles, and corundum enriched particles. The corundum skeleton particles have a particle size of 10–60 μm, a D50 of 20–38 μm, and a D90 of no more than 55 μm.

[0008] Furthermore, the apparent thickness of the yttrium-rich aluminum inner reaction zone is 0.2–3.0 μm, and the apparent thickness of the aluminum-silicon crystal outer reaction zone is 0.8–7.0 μm; The yttrium-rich aluminum inner reaction zone and the aluminum-silicon crystal outer reaction zone are distributed continuously, segmentally continuously, or partially interrupted along the circumference of the corundum skeleton particles. The identifiable cumulative coverage of at least one of the yttrium-rich aluminum inner reaction zone and the aluminum-silicon crystal outer reaction zone along the circumference of the corundum skeleton particles is 40% to 85%.

[0009] Furthermore, in the fired ceramic body, the yttrium component, calculated as Y2O3, accounts for 0.08% to 0.80% of the total dry weight of the fired ceramic body; The amount of corundum framework particles is 12 to 28 parts by mass relative to 100 parts by mass of the main ceramic material forming the aluminosilicate continuous matrix.

[0010] Furthermore, the yttrium-rich aluminum inner reaction zone includes one or more of the following: yttrium aluminum oxide, yttrium aluminum silicon composite reaction phase, aluminum-rich glass phase, and fine alumina grains; The aluminum-silicon crystals in the outer reaction zone of the aluminum-silicon crystals include secondary mullite crystals formed or continuing to develop during the firing process. The secondary mullite crystals are distributed in one or more of the following morphologies: short rod-shaped, elliptical, dot-shaped, and needle-shaped.

[0011] This invention also provides a method for preparing rare-earth modified high-strength porcelain insulators, comprising the following steps: The corundum skeleton particles are screened, washed, and dried. The corundum framework particles are coated with an inner layer precursor slurry containing yttrium and aluminum sources to form a yttrium-rich aluminum inner layer on the surface of the corundum framework particles. A corundum skeleton particles with a yttrium-rich aluminum inner layer are coated with an outer layer precursor slurry containing aluminum and silicon sources. An aluminum-silicon outer layer is formed on the outside of the yttrium-rich aluminum inner layer. Then, drying and pre-fixing treatment are performed to obtain double-layer coated corundum skeleton particles. The main ceramic material used to form the aluminosilicate continuous matrix is ​​separately wet ball-milled, and the double-layer coated corundum skeleton particles are not added during the wet ball milling of the main ceramic material; After the main ceramic material is wet ball milled, the double-layer coated corundum skeleton particles are added to the main ceramic material and mixed with low shear to obtain a mixed ceramic material. The mixed ceramic material is dehydrated, and the dehydrated mixed ceramic material is kneaded and aged or granulated according to the molding method. Then it is molded, dried and glazed to obtain an insulator blank. The insulator blank is heated to the peak firing temperature and held at that temperature to densify the insulator blank. After holding at the peak firing temperature, the insulator blank is cooled to an interface reaction temperature lower than the peak firing temperature, and then held at the interface reaction temperature. Subsequently, controlled cooling is performed to obtain the rare earth modified high-strength porcelain insulator. After firing, at least some of the corundum skeleton particles form a rare earth modified reaction transition structure between the fired aluminosilicate continuous matrix and the corundum skeleton particles. Along the direction of the corundum skeleton particles toward the aluminosilicate continuous matrix, the rare earth modified reaction transition structure sequentially includes a yttrium-rich aluminum inner reaction zone and an aluminum-silicon crystal outer reaction zone.

[0012] Furthermore, based on a dry basis of 100 parts by weight, the main ceramic material comprises 32-45 parts of calcined bauxite, 18-28 parts of kaolin, 8-16 parts of plastic clay, 8-16 parts of feldspar, 3-9 parts of quartz, 6-16 parts of fine-grained alumina, and 0.3-2.0 parts of mineralized components, with the total amount of each component being 100 parts. The mineralized components include at least one of talc and dolomite; The amount of corundum skeleton particles added is 12 to 28 parts by weight relative to 100 parts by weight of the main ceramic material.

[0013] Furthermore, based on 100 parts by weight of the corundum skeleton particles, the solid components in the inner layer precursor slurry include 2 to 8 parts of aluminum source converted to Al2O3, 0.4 to 2.4 parts of yttrium source converted to Y2O3, and 0.1 to 0.8 parts of film-forming agent; The yttrium source includes one or more of yttrium nitrate, yttrium acetate, yttrium carbonate dispersion, and yttrium oxide sol, and the aluminum source includes one or more of boehmite sol, alumina sol, nano alumina powder, and submicron alumina powder; Based on 100 parts by weight of the corundum skeleton particles, the solid components in the outer layer precursor slurry include 3-8 parts of metakaolin, 2-8 parts of fine alumina, 0-1.5 parts of silica sol solids, and 0.1-0.6 parts of film-forming agent or dispersant. The mass ratio of Al2O3 to SiO2 in the outer layer precursor slurry is 2.0 to 3.2.

[0014] Furthermore, the pre-fixation treatment temperature of the double-layer coated corundum skeleton particles is 650-850℃, and the holding time is 30-120min. The slurry formed by wet ball milling of the main ceramic material has a D50 of 1.5–4.5 μm and a sieve residue of no more than 0.5% on a 45 μm sieve. After the double-layer coated corundum skeleton particles are added to the main ceramic material, they are mixed under low shear at a speed of 30-100 r / min for 5-20 min.

[0015] Furthermore, the peak firing temperature is 1260–1325°C, and the holding time at the peak firing temperature is 10–45 min; After holding at the peak firing temperature, the temperature is reduced to 1160-1220℃ at a rate of 1-4℃ / min, and held at 1160-1220℃ for 30-120min. After maintaining the temperature at the interface reaction temperature, cool the temperature to below 900℃ at a cooling rate of 2-5℃ / min, and then allow it to cool naturally.

[0016] Compared with the prior art, the present invention has the following beneficial effects.

[0017] This invention incorporates a yttrium-rich aluminum inner reaction zone and an aluminum-silicon crystal outer reaction zone between corundum framework particles and an aluminosilicate continuous matrix. The yttrium-rich aluminum inner reaction zone is located on the surface of the corundum framework particles, while the aluminum-silicon crystal outer reaction zone is located between the yttrium-rich aluminum inner reaction zone and the continuous matrix, creating a gradual transition between the corundum framework particles and the continuous matrix. This structure reduces local porosity and abrupt compositional changes at the edges of the corundum framework particles, mitigating localized stresses formed after firing and cooling. When the ceramic body is under stress, the corundum framework particles can share the load, and the reaction zone around the particles can deflect or branch cracks, thereby improving the bonding state, mechanical strength, and stability after temperature changes in the ceramic body. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the preparation method of the rare earth modified high-strength porcelain insulator of the present invention; Figure 2This is a backscattered electron micrograph of the corundum skeleton particles and the surrounding interface reaction zone in the cross-section of the rare earth modified high-strength porcelain insulator of the present invention. Figure 3 for Figure 2 Energy spectrum surface scan distribution of yttrium, aluminum, and silicon in the region shown; Figure 4 This is a graph showing the trend of relative elemental content obtained by energy dispersive spectroscopy (EDS) scans along the directions of corundum skeleton particles, interfacial reaction zone, and aluminosilicate matrix. Detailed Implementation

[0019] Reference Figures 1 to 4 The present invention will be further described below in conjunction with the raw material composition, preparation process, comparative examples, and test results. All mass parts are on a dry basis. Unless otherwise specified, deionized water is used, and the Al2O3 content of the corundum framework particles used is not less than 95%, with α-Al2O3 as the main crystalline phase. After sieving, the corundum framework particles are irregularly angular to sub-circular in shape. The particle edges may have straight surfaces, rounded corners, and shallow notches; a regular spherical shape is not required.

[0020] This invention retains corundum framework particles of a certain particle size. These particles bear part of the load in the ceramic body and can also cause cracks to bypass or change direction. When the particles are too fine, their role in bearing load and changing crack paths is not obvious; when the particles are too large, the surrounding ceramic material is not easily filled, and local stress is easily generated during cooling. Therefore, the particle size of the corundum framework particles is controlled at 10-60 μm, D50 is controlled at 20-38 μm, and D90 is not greater than 55 μm. In the embodiment, 16-23 parts by weight of corundum framework particles are added to 100 parts by weight of the main ceramic material, which retains the role of the particles while avoiding excessive particles that would cause the clay to disperse, making molding difficult and causing firing deformation.

[0021] A yttrium-rich aluminum inner layer first forms on the surface of the corundum framework particles, followed by an aluminum-silicon outer layer. The yttrium and aluminum sources in the yttrium-rich aluminum inner layer are initially located close to the corundum surface. During firing, yttrium does not need to reach a high content throughout the entire ceramic body, but is mainly retained at the particle edges. The aluminum-silicon outer layer is located between the yttrium-rich aluminum inner layer and the main ceramic material. This outer layer forms aluminum-silicon crystals, primarily secondary mullite crystals, during firing and cooling / holding. In this way, the corundum framework particles do not directly contact a large amount of glass phase, and a gradual transition from the aluminum-rich region to the aluminum-silicon region is formed between the particles and the continuous matrix.

[0022] After the double-layer coated particles are formed, they undergo pre-fixation. Pre-fixation removes organic matter from the coating slurry, decomposes the yttrium source, and allows the inner and outer layers to initially bond on the particle surface. If the pre-fixation temperature is too low, the coating layer is prone to detachment during subsequent wet mixing; if the temperature is too high, the outer layer will sinter prematurely, affecting subsequent contact and reaction with the main ceramic material. In this example, the pre-fixation temperature is controlled at 720–800°C. After pre-fixation, only slight sieving is performed, and high-energy grinding is no longer used.

[0023] The main ceramic material and the double-layered coated corundum framework particles are processed separately. The main ceramic material is first wet-milled to a D50 of 1.5–4.5 μm, with a 45 μm sieve residue not exceeding 0.5%. After ball milling, the double-layered coated corundum framework particles are added for low-shear mixing. This sequence prevents the corundum framework particles from becoming too fine and reduces the amount of inner and outer layers that are ground away by the milling media. Low-shear mixing is only used to disperse the particles into the main slurry and is not intended for further pulverization.

[0024] The firing process employs two holding stages. First, a short holding period is maintained at the peak firing temperature of 1260–1325℃ to allow the main ceramic material to form a liquid phase and close its pores. Then, the temperature is lowered to 1160–1220℃ for interfacial reaction holding. After cooling, the liquid phase flow weakens, reducing the rate of yttrium diffusion to distant locations, while the aluminum-silicon outer layer can continue to react and precipitate aluminum-silicon crystals. By separately completing overall densification and interfacial structure development, yttrium diffusion, glassy phase segregation, and green body deformation caused by prolonged peak holding can be reduced.

[0025] Table 1 Basic Formula of Main Ceramic Material

[0026] Each raw material in Table 1 was first de-ironized and sieved. Calcined bauxite, kaolin, plastic clay, potassium-sodium feldspar, quartz, fine-grained alumina, and talc together constituted the main ceramic material. The composition of the main ceramic material remained consistent in all examples and comparative examples. The main adjustments between the examples were made to the amount of corundum framework particles, the amount of coating layer, the pre-fixation conditions, and the firing conditions, thereby comparing the effects of these conditions on the interfacial structure and ceramic properties.

[0027] Table 2 Main process parameters of the examples Example 1

[0028] Sintered corundum particles with a D50 of 24 μm and a D90 of 42 μm were weighed. The particles were placed in softened water, and a neutral dispersant equivalent to 0.10% of the washing water mass was added. The mixture was stirred at 60 rpm for 10 min, allowed to stand, and the supernatant was drained. The particles were then rinsed twice with deionized water. The rinsed corundum particles were dried at 100℃ for 2 h until the moisture content decreased to 0.25%. The washing process was used to remove surface dust and loose fine powder from the particles, preventing the coating slurry from adhering only to the surface dust.

[0029] Based on 100 parts by weight of corundum framework particles, take 1.05 parts by weight of yttrium nitrate solution (converted to Y₂O₃); take 3.8 parts by weight of boehmite sol (converted to Al₂O₃); and add 0.25 parts by weight of polyvinyl alcohol. Adjust the slurry solids content to 15% and the pH to 5.4 with deionized water. First, place the corundum framework particles in a roller coating machine and rotate it at 25 r / min. Then, spray the inner layer precursor slurry evenly in three stages. After each spraying, continue rolling for 5 minutes to spread the slurry. After spraying is complete, continue rolling for 15 minutes and dry at 90℃ for 60 minutes. Adding in stages can reduce soft agglomeration caused by excessive local slurry.

[0030] 4.5 parts by weight of metakaolin, 4.0 parts by weight of fine alumina, and 0.20 parts by weight of ammonium polyacrylate were dispersed in water to prepare an outer layer precursor slurry with a solid content of 20%. Based on the composition analysis of the metakaolin and fine alumina used, the mass ratio of Al2O3 to SiO2 in the outer layer precursor was 2.52. The particles with the yttrium-rich aluminum inner layer were placed back into a roller coating machine and slowly sprayed into the outer layer slurry at a speed of 25 r / min. The spraying time was 10 min, followed by another 10 min of rolling. The resulting particles were dried at 100℃ for 2 h, and then pre-fixed at 720℃ for 45 min. After pre-fixation, the particles were lightly sieved through a 60-mesh sieve to remove a small amount of soft agglomerates.

[0031] The main ceramic material was weighed according to Table 1. The mass ratio of the main ceramic material, high-alumina balls, and water was 1:1.6:0.7, and wet ball milling was performed for 8 hours. After ball milling, the slurry D50 was 3.2 μm, and the residue on a 45 μm sieve was 0.36%. Double-layered coated corundum framework particles were not added during ball milling. Subsequently, 16 parts by mass of double-layered coated corundum framework particles were added per 100 parts by mass of main ceramic material, and the mixture was stirred for 10 minutes at 50 r / min using a paddle mixer. After mixing, samples were taken for observation; no large number of independent coated fragments were observed, and the particles remained basically independently dispersed.

[0032] The mixed slurry was dewatered by pressure filtration, and the moisture content of the filter cake was controlled at 21.5%. The filter cake was kneaded twice under a vacuum of -0.092 MPa and then sealed and aged for 24 hours. Kneading was used to remove larger air bubbles and to fill the corundum skeleton particles with fine ceramic particles. The number of kneading cycles was not increased to avoid subjecting the double-layered coated particles to repeated strong shearing. The aged clay was extruded into clay segments and then used to make unglazed test strips of 3mm×4mm×36mm, dielectric test pieces of approximately 2mm thickness, and small columnar insulator blanks.

[0033] The green body was first dried at 45℃ for 12 hours, then dried at 90℃ for 8 hours to reduce the moisture content to below 0.5%. Small insulator green bodies were glazed using an electrical porcelain glaze that matched the thermal expansion state of the porcelain body. Samples for testing the porosity and microstructure of the porcelain body were not glazed. During firing, the green body underwent conventional drainage and binder removal, then heated to 1285℃ and held for 20 minutes; subsequently, it was cooled to 1190℃ at a rate of 2.5℃ / min and held for 50 minutes; after the holding period, it was cooled to 900℃ at a rate of 3℃ / min and then allowed to cool naturally in the furnace. The peak holding period was used to achieve overall densification, while the cooling holding period was used to allow the aluminum-silicon outer layer to continue reacting and to reduce the diffusion of yttrium into the distant matrix.

[0034] After firing, the corundum framework particles are dispersed in a continuous aluminosilicate matrix. The edges of most larger particles reveal a yttrium-rich aluminum-rich inner reaction zone and an aluminum-silicon crystal-rich outer reaction zone. These two reaction zones are segmented and continuous along the circumference of the particles, with interruptions at local sharp corners and particle contact points. Short rod-shaped and dot-shaped aluminum-silicon crystals are visible within the outer reaction zone. Example 2

[0035] Sintered corundum particles with a D50 of 30 μm and a D90 of 49 μm were weighed. They were cleaned according to the method in Example 1, and then dried at 100°C for 2 hours until the moisture content was 0.22%. Compared to Example 1, the particle size and amount added were appropriately increased to allow the particles to form clearer supporting units in the continuous matrix, while still ensuring that the main ceramic material could fill the spaces between the particles.

[0036] Based on 100 parts by weight of corundum framework particles, yttrium nitrate solution was measured as 1.55 parts by weight (based on Y₂O₃ equivalent), boehmite sol as 4.6 parts by weight (based on Al₂O₃ equivalent), and 0.35 parts by weight of polyvinyl alcohol were added. The solid content of the inner layer precursor slurry was adjusted to 17% and the pH to 5.6 with water. The slurry was sprayed in three stages using a roller coating method, with a roller speed of 28 r / min and a total coating time of 18 min. After coating, it was dried at 90℃ for 70 min. This dosage ensures that yttrium and aluminum components are stably located on the surface of the corundum particles without forming obvious thick lumps.

[0037] The outer layer precursor slurry consists of 5.0 parts by weight of metakaolin, 4.5 parts by weight of fine alumina, and 0.25 parts by weight of ammonium polyacrylate, with a solid content of 21% and an Al2O3 to SiO2 mass ratio of 2.54. It is coated using a roller at 28 r / min for 20 min and dried at 100℃ for 2 h. The double-coated particles are pre-fixed at 760℃ for 60 min, cooled, and then lightly sieved. This temperature allows the coating layer to achieve good wet mixing resistance without making the outer layer completely dense.

[0038] The mass ratio of the main ceramic material, high-alumina balls, and water was 1:1.6:0.7, and wet ball milling was performed for 9 hours. The resulting slurry had a D50 of 2.8 μm and a 45 μm sieve residue of 0.28%. After ball milling the main ceramic material, 20 parts by mass of double-layered coated corundum framework particles were added per 100 parts by mass of the main ceramic material, and the mixture was low-shear mixed at 55 r / min for 12 min. The main ceramic material has a relatively fine particle size, which can fill the area around the corundum framework particles; the double-layered coated particles were added after ball milling to prevent them from being further ground.

[0039] The mixed slurry was filtered to a moisture content of 21.0%, then vacuum-kneaded twice at -0.094 MPa and sealed for aging for 24 hours. Test strips, test pieces, and small columnar insulator blanks were prepared using the same method as in Example 1. The blanks were first dried at 40°C for 10 hours, then at 55°C for 8 hours, and finally at 95°C for 6 hours. Staged drying can reduce drying cracks caused by different water loss rates between the inner and outer layers when there are many particles.

[0040] The billet was heated to 1300℃ and held for 25 minutes, then cooled to 1200℃ at a rate of 2.0℃ / min and held for 70 minutes. After the interfacial reaction was completed, it was cooled to 900℃ at a rate of 3℃ / min, and then allowed to cool naturally in the furnace. In this embodiment, the peak temperature ensured sufficient densification of the main matrix without significantly extending the peak holding time. The cooling and holding at 1200℃ allowed the outer aluminum-silicon crystals to continue developing, while retaining a relatively clear interfacial yttrium enrichment.

[0041] Figures 2 to 4 The porcelain body obtained in Example 2 was used for observation. Figure 2 The larger irregular particles shown are corundum skeletal particles, while the surrounding fine grains and short rod-shaped structures are interfacial reaction structures. Figure 3 In this study, yttrium is mainly found at the edges of corundum skeletal particles, aluminum is abundant in corundum particles and their inner reaction zones, and silicon is mainly distributed in the outer reaction zones and the aluminosilicate continuous matrix. Figure 4 The relative variations of Y, Al, and Si elements are represented from the interior of the corundum framework grains towards the continuous matrix. Region I corresponds to the corundum framework grains, Region II corresponds to the yttrium-rich aluminum-containing inner reaction zone, Region III corresponds to the aluminum-containing silicon crystal outer reaction zone, and Region IV corresponds to the aluminosilicate continuous matrix. P1, P2, and P3 represent the boundaries between adjacent regions. Figure 4 It is used to illustrate the trend of elemental change, not to compare the absolute content of the three elements.

[0042] In the polished cross-section of Example 2, the apparent thickness of the yttrium-rich aluminum inner reaction zone is 0.7–1.2 μm, and the apparent thickness of the aluminum-silicon crystal outer reaction zone is 2.8–4.5 μm. The identifiable cumulative circumferential coverage of the reaction zone is 68%. The aluminum-silicon crystals in the outer reaction zone are mainly short rod-shaped, elliptical, and dot-shaped, with a small number of needle-shaped cross-sections. There is a gradual transition between them and the distal continuous matrix, without forming a straight boundary line. Example 3

[0043] Fused corundum particles with a D50 of 36 μm and a D90 of 54 μm were weighed. They were cleaned using the same method as in Example 1 and dried at 110°C for 2 hours. Based on 100 parts by weight of corundum skeleton particles, 2.05 parts by weight of yttrium nitrate solution (based on Y2O3 equivalent) and 5.2 parts by weight of alumina sol (based on Al2O3 equivalent) were added as a film-forming agent. The inner layer precursor slurry had a solid content of 19% and a pH of 5.8. Coating was performed using a combination of low-speed paddle stirring and spraying. The stirring speed was 45 r / min, and stirring continued for 12 minutes after spraying, followed by drying at 95°C for 90 minutes.

[0044] The outer precursor slurry consists of 5.5 parts by weight of metakaolin, 5.0 parts by weight of fine-grained alumina, and 0.30 parts by weight of ammonium polyacrylate, with a solid content of 22% and an Al2O3 to SiO2 mass ratio of 2.56. After coating, it is dried at 105°C for 2 hours and pre-fixed at 800°C for 75 minutes. In Example 3, the coating amount is higher, and the pre-fixing temperature is correspondingly increased to reduce the shedding of the thicker coating layer during wet mixing.

[0045] The main ceramic material was wet-milled to a D50 of 2.4 μm, with a 45 μm sieve residue of 0.22%. 23 parts by weight of double-layered coated corundum skeleton particles were added to every 100 parts by weight of the main ceramic material, and the mixture was stirred at 60 r / min for 12 min. After pressure filtration, the slurry was vacuum-kneaded at -0.095 MPa and sealed for 36 h of aging. Test strips, test pieces, and small insulator blanks were prepared using the same method as in Example 1. Due to the high amount of corundum skeleton particles, the moisture content of the slurry was controlled at 21.8% during kneading and molding to ensure that the particles were surrounded by fine particles.

[0046] After staged drying and glazing, the green body was heated to 1310℃ and held for 20 minutes, then cooled to 1210℃ at a rate of 1.8℃ / min and held for 80 minutes. It was then cooled to 900℃ at a rate of 2.5℃ / min and allowed to cool naturally in the furnace. After firing, a relatively thick yttrium-rich aluminum inner reaction zone and an aluminum-silicon crystal outer reaction zone were formed, with high circumferential coverage. Due to the increased amount of corundum framework particles, inner and outer layer precursors, and local liquid phase, the difficulty of clay filling and firing deformation also increased slightly. These results indicate that adding more corundum framework particles and yttrium sources is not necessarily better; it should be coordinated with the filling capacity of the main ceramic material and the firing regime.

[0047] In addition to the plastic molding methods mentioned above, the mixed slurry can also be spray-granulated and then subjected to isostatic pressing or compression molding. When using spray granulation, the inlet air temperature and slurry residence time should be controlled to prevent the double-layer coating on the particle surface from falling off due to prolonged cyclic shearing. When using disc-type, rod-type, pillar-type, or circuit column-type structures, the drying time of the green body and the firing temperature rise time can be adjusted according to the product size, but the order of adding the corundum skeleton particles later, low-shear mixing, peak short-time heat preservation, and cooling interface reaction heat preservation remains unchanged.

[0048] Comparative Example 1 Comparative Example 1 used the main ceramic material shown in Table 1. 20 parts by weight of uncoated sintered corundum particles with a D50 of 30 μm were added per 100 parts by weight of the main ceramic material. No yttrium source was added, and no yttrium-rich aluminum inner layer or aluminum-silicon outer layer was formed. The corundum particles, along with the main ceramic material, high-alumina balls, and water, were wet-milled for 6 hours, followed by dehydration, kneading, aging, shaping, drying, and glazing as described in Example 2. The firing regime involved holding at 1300°C for 25 minutes, then cooling to 1200°C and holding for 70 minutes. This group represents the state of directly adding corundum particles to ordinary high-alumina ceramic materials.

[0049] Comparative Example 2 Comparative Example 2 used the same amount of main ceramic material and corundum framework particles as Example 2. Based on the total amount calculated in Example 2, 0.31 parts by weight of Y₂O₃ were directly added to 100 parts by weight of the main ceramic material. To reduce the difference in the overall composition of the raw materials, the aluminum source, metakaolin, and fine alumina particles corresponding to the coating layer in Example 2 were also added to the main ceramic material in equal amounts. All raw materials and corundum particles were wet-ball milled together for 6 hours, without double-layer coating or pre-fixation of the particle surface. The remaining molding and firing conditions were the same as in Example 2. This group was used to compare the differences in the dispersion of the same total amount of rare earth elements in the entire matrix and their positioning at the corundum particle interface.

[0050] Comparative Example 3 Comparative Example 3 prepared double-layer coated corundum framework particles according to the method of Example 2, and pre-fixed them at 760°C for 60 min. Unlike Example 2, the pre-fixed double-layer coated corundum framework particles were added to the ball mill at the beginning of the wet ball milling of the main ceramic material, and ball-milled together with the main ceramic material for 6 h. After ball milling, dehydration, clay preparation, shaping, and staged firing were carried out according to the method of Example 2. This group was used to observe the effect of co-ball milling on the coating layer and the particle size of the corundum framework particles.

[0051] Comparative Example 4 Comparative Example 4 formed a yttrium-rich aluminum inner layer on the surface of corundum framework particles according to the method of Example 2, and pre-fixed it at 760°C for 60 min, but did not form an aluminum-silicon outer layer on its outer surface. To reduce the difference in overall composition, the metakaolin and fine-grained alumina used in the outer layer of Example 2 were added to the main ceramic material in equal amounts. The yttrium-rich aluminum inner layer particles were added after the main ceramic material was ball-milled and mixed at 55 r / min for 12 min. The remaining molding and firing conditions were the same as in Example 2. This group was used to observe the compositional buffer formed by the aluminum-silicon outer layer and the effect of the aluminum-silicon crystals on the interface state.

[0052] Comparative Example 5 The raw materials, double-layer coating, pre-fixation, separate ball milling of the main ceramic material, subsequent addition, and low-shear mixing of Comparative Example 5 were all the same as in Example 2. During firing, the temperature was raised to 1300℃ and held for 90 minutes, without further cooling to 1200℃ for interfacial reaction holding. After the peak holding period, the temperature was directly cooled to 900℃ at a rate of 3℃ / min, and then allowed to cool naturally in the furnace. This group was used to compare the differences between long-duration peak holding and staged firing.

[0053] Test methods Each group underwent three batches of mixing and firing. For room temperature flexural strength testing, 15 effective specimens were taken from each group; for water absorption and apparent porosity testing, 5 specimens were taken from each group; for thermal shock testing, 8 specimens were taken from each group; for dielectric breakdown testing, 8 specimens were taken from each group; and for firing deformation, 5 specimens were taken from each group. Microstructure was measured from samples close to the average flexural strength of each group, and multiple particles and fields of view were observed.

[0054] The room-temperature flexural strength was tested using 3mm×4mm×36mm rectangular specimens with a support span of 30mm and a loading rate of 0.5mm / min. The failure load of each specimen was recorded, and the flexural strength was calculated. Fifteen valid results were used for two-parameter Weibull fitting. A higher Weibull modulus indicates smaller strength fluctuations among specimens in the same group.

[0055] Water absorption and apparent porosity were determined using the boiling water absorption method. First, the unglazed sample was dried to constant weight, and the dry mass was recorded. Then, the sample was boiled in water until fully saturated, and the saturated mass and the suspended mass in water were recorded. Water absorption and apparent porosity were calculated based on these three masses. Samples from the same batch of unglazed samples were used to avoid the glaze layer sealing the surface pores and affecting the results of the porcelain itself.

[0056] In the thermal shock test, the specimen was placed in an oven at 180℃ for 30 minutes, then quickly immersed in water at 20±3℃, cooled for 10 minutes, and then removed and dried. This process was repeated 5 times. After 5 cycles, the surface and edges of the specimen were checked for cracks, and the residual flexural strength was determined using the same three-point bending method. The ratio of the average strength after thermal shock to the average strength before thermal shock was taken as the strength retention rate.

[0057] Dielectric breakdown strength was tested using a fired ceramic disc approximately 2 mm thick. The sample was placed in insulating oil, and a spherical electrode was used to increase the voltage at a rate of approximately 0.5 kV / s until breakdown occurred. The dielectric breakdown strength was obtained by dividing the breakdown voltage by the actual thickness of the sample. Firing deformation was evaluated using an unglazed test strip approximately 100 mm long. The test strip was supported at both ends and fired in the same kiln as the product. The deflection at the center after firing was measured and then converted into bending per meter of length.

[0058] Microstructure samples were cut, mounted, progressively ground, and polished with a 1μm diamond suspension. Backscattered electron microscopy (BEP) was used to observe the corundum framework particles and surrounding reaction structures. Surface scans, point analyses, and line scans of Y, Al, and Si were performed in the same region. The thickness of the yttrium-rich aluminum-rich inner reaction zone was measured from the edge of the corundum particles outwards; the thickness of the aluminum-silicon crystal outer reaction zone was determined based on the fine grain, short rod-shaped crystal structure, and variations in Al and Si composition. Each measurement group included at least 20 effective interface locations. Identifiable circumferential coverage was calculated as the ratio of the length of the periphery of particles from which the inner or outer reaction structures could be identified to the total length of the periphery of visible particles.

[0059] X-ray diffraction was used to identify α-Al₂O₃, mullite, and residual quartz in the fired ceramic body. The scanning range was 10°–80°. Because the yttrium-rich aluminum inner reaction zone is relatively thin, the X-ray diffraction results were mainly used to identify the overall crystal phase, and the inner reaction zone was not limited to a specific compound based solely on the overall diffraction peaks.

[0060] Test Results and Analysis

[0061] As shown in Table 3, Comparative Example 1 did not form a yttrium-rich aluminum-enriched inner reaction zone. Only a narrow and unstable aluminum-silicon reaction structure appeared at the edges of the corundum particles, with an identifiable circumferential coverage of 18%. Although Comparative Example 2 added a total yttrium component similar to that of Example 2, the yttrium was dispersed in a continuous matrix, and the Y signal at the edges of the corundum particles was only slightly higher than that at the distal matrix, failing to form a clear interface enrichment. This indicates that the same total rare earth element content does not necessarily equate to the same interface state.

[0062] Comparative Example 3 underwent double-layer coating and pre-fixation, but the double-coated particles were ball-milled together with the main ceramic material. The ball milling media caused collisions and friction on the particle surface, leading to partial detachment of the coating layer and further refinement of the corundum framework particles. Consequently, its inner reaction zone was relatively thin, with a circumferential coverage of only 34%, and the difference between the Y-peak and the distal matrix was also small. This result indicates that separate ball milling of the main ceramic material, subsequent addition of double-coated particles, and low-shear mixing require coordinated processes.

[0063] Comparative Example 4 retained the yttrium-rich aluminum inner layer, with a more pronounced interfacial Y-peak, but no aluminum-silicon outer layer formed outside the inner layer. After firing, fewer short rod-shaped aluminum-silicon crystals were found on the outer side, and the thickness and coverage of the outer reaction zone were lower than in Example 2. Comparative Example 5 employed a long peak holding time. Although this group was able to continue densification, yttrium diffused outward in the high-temperature liquid phase, causing the interfacial Y-peak to decrease, and the local liquid phase flow time to increase. This indicates that extending the peak holding time cannot replace the interfacial reaction holding time after cooling.

[0064] Examples 1 through 3 all formed an inner reaction zone containing yttrium-rich aluminum and an outer reaction zone containing aluminum-silicon crystals. Example 1 used lower dosages and reaction times, resulting in a thinner reaction zone and more local interruptions. Example 2 showed a more balanced distribution of inner and outer reaction zone thickness, circumferential coverage, and yttrium enrichment. Example 3 increased the dosage of framework particles and the coating layer, further improving circumferential coverage, but the outer reaction zone became thicker, and the amount of liquid phase in some areas also increased.

[0065] Table 4. Test results of strength, porosity, and strength dispersion for each group.

[0066] Table 5. Results of thermal shock, electrical performance and firing deformation tests for each group.

[0067] As shown in Tables 4 and 5, in Comparative Example 1, when corundum particles and the main ceramic material were ball-milled together, the particle edges lacked a stable reactive transition structure, resulting in lower flexural strength and Weibull modulus, an apparent porosity of 1.10%, and a strength retention rate of 71.8% after thermal shock. This indicates that simply adding corundum particles to high-alumina ceramic material cannot stably solve the problems of particle edge bonding and stress concentration.

[0068] Comparative Example 2 used the same total amount of yttrium component directly added to the main ceramic material. Its flexural strength and dielectric breakdown strength were higher than those of Comparative Example 1 (which did not contain yttrium), but lower than those of Examples 1 to 3. The Y element interface peak in this group was not obvious, indicating that although the uniform dispersion of the yttrium component can affect the overall sintering, a small amount of yttrium is unlikely to preferentially act around the corundum framework particles.

[0069] In Comparative Example 3, the double-layered coated particles participated in co-ball milling, which disrupted the spatial position of the coating layers. This group showed a decrease in water absorption and apparent porosity, but its flexural strength, Weibull modulus, and post-thermal shock strength retention were still lower than those of the complete process. This indicates that the coating structure not only needs to be formed first but also needs to be retained in subsequent mixing.

[0070] Comparative Example 4 formed a yttrium-rich aluminum inner layer. Its flexural strength was 208.7 MPa, and the strength retention rate after thermal shock was 80.8%. Compared with Comparative Examples 2 and 3, its performance was improved, but still lower than Example 2. This result is consistent with microscopic observation. The yttrium-rich aluminum inner layer can improve the state near the corundum surface, but without the outer aluminum-silicon crystal structure, the compositional transition between the corundum particles and the continuous matrix is ​​still insufficient.

[0071] Comparative Example 5 was held at 1300℃ for 90 min. The apparent porosity of this group was 0.71%, indicating that prolonged peak holding time could further densify the ceramic body. However, its firing deformation increased to 3.3 mm·m. -1 The interface Y-peak decreased, and the flexural strength and post-thermal shock strength retention rate were both lower than in Example 2. This indicates that prolonged peak insulation simultaneously increases rare earth diffusion and liquid phase flow, and cannot simply replace interfacial reaction insulation at lower temperatures.

[0072] The flexural strength of Examples 1 to 3 was 229.4–244.1 MPa, the apparent porosity was 0.49%–0.60%, the strength retention rate after thermal shock was 85.0%–88.1%, and the dielectric breakdown strength was 19.4–20.2 kV·mm. -1 The three sets of data did not show a continuous unidirectional increase with the amount of yttrium component and corundum particles. In Example 3, the amount of corundum particles and the coating layer were higher than in Example 2, but the average flexural strength and Weibull modulus decreased slightly, while the firing deformation increased. This indicates that higher dosages increase the difficulty of interparticle filling and the amount of localized liquid phase.

[0073] Example 2 exhibits a relatively balanced performance in terms of flexural strength, strength dispersion, post-thermal shock strength retention, dielectric breakdown strength, and firing deformation. Its yttrium-rich aluminum-containing inner reaction zone is adjacent to the corundum framework particles, while the aluminum-silicon crystal-containing outer reaction zone is located between the inner reaction zone and the continuous aluminosilicate matrix. Neither requires the formation of a complete, uniformly thick closed layer, but both are identifiable around a significant proportion of the particle periphery. This structure reduces porosity and compositional abrupt changes at the corundum particle edges, allowing the particles to share the load under stress and making it easier for cracks to deflect or branch around the particle periphery.

[0074] In other embodiments, the corundum framework particles can be fused corundum, sintered corundum, calcined alumina particles, or corundum-enriched particles. The yttrium source can be yttrium nitrate, yttrium acetate, yttrium carbonate dispersion, or yttrium oxide sol. The aluminum source can be boehmite sol, alumina sol, nano-alumina powder, or submicron alumina powder. The aluminum-silicon outer layer can be made of two or more of metakaolin, calcined kaolin, kaolin, silica sol, and fine-grained alumina. As long as the inner layer is located on the surface of the corundum particles and the outer layer is located outside the inner layer, and the corresponding spatial order is maintained through pre-fixation, subsequent addition of low shear, and staged firing, a corresponding rare earth modification reaction transition structure can be formed after firing.

[0075] The above embodiments illustrate the preparation process and testing method of the present invention. In actual production, the drying time, heating time, and holding time can be adjusted within the range described, according to the insulator size, kiln load, and molding method. Adjustments should be made to maintain the particle size of the corundum skeleton, the spatial order of the double-layer coating, and the inner and outer reaction zones after firing.

Claims

1. A rare-earth modified high-strength porcelain insulator, characterized in that, The porcelain insulator is a high-alumina special ceramic insulating product for electrical use in power transmission and distribution equipment. It includes a porcelain body, and the fired porcelain body includes an aluminosilicate continuous matrix and corundum skeleton particles dispersed in the aluminosilicate continuous matrix. At least some of the corundum framework particles and the aluminosilicate continuous matrix form a rare earth modified reaction transition structure; Along the direction of the corundum skeleton particles toward the aluminosilicate continuous matrix, the rare earth modified reaction transition structure sequentially includes an inner reaction zone containing yttrium-rich aluminum and an outer reaction zone containing aluminum-silicon crystals. The yttrium-rich aluminum inner reaction zone is adjacent to the corundum skeleton particles. The yttrium-rich aluminum inner reaction zone contains yttrium and aluminum, and the yttrium content in the yttrium-rich aluminum inner reaction zone is higher than the yttrium content in the aluminosilicate continuous matrix. The outer reaction zone of the aluminum-containing silicon crystal is located between the yttrium-rich aluminum inner reaction zone and the continuous aluminum silicate matrix, and aluminum-containing silicon crystals are distributed in the outer reaction zone of the aluminum-containing silicon crystal.

2. The rare earth modified high-strength porcelain insulator according to claim 1, characterized in that, The corundum framework particles have α-Al2O3 as the main crystalline phase, and the Al2O3 content of the corundum framework particles is not less than 90%. The corundum skeleton particles are one or more of the following: fused corundum particles, sintered corundum particles, calcined alumina particles, and corundum enriched particles. The corundum skeleton particles have a particle size of 10–60 μm, a D50 of 20–38 μm, and a D90 of no more than 55 μm.

3. The rare earth modified high-strength porcelain insulator according to claim 1, characterized in that, The apparent thickness of the yttrium-rich aluminum inner reaction region is 0.2–3.0 μm, and the apparent thickness of the aluminum-silicon crystal outer reaction region is 0.8–7.0 μm. The yttrium-rich aluminum inner reaction zone and the aluminum-silicon crystal outer reaction zone are distributed continuously, segmentally continuously, or partially interrupted along the circumference of the corundum skeleton particles. The identifiable cumulative coverage of at least one of the yttrium-rich aluminum inner reaction zone and the aluminum-silicon crystal outer reaction zone along the circumference of the corundum skeleton particles is 40% to 85%.

4. The rare earth modified high-strength porcelain insulator according to claim 1, characterized in that, In the fired ceramic body, the yttrium component, calculated as Y2O3, accounts for 0.08% to 0.80% of the total dry weight of the fired ceramic body; The amount of corundum framework particles is 12 to 28 parts by mass relative to 100 parts by mass of the main ceramic material forming the aluminosilicate continuous matrix.

5. The rare earth modified high-strength porcelain insulator according to claim 1, characterized in that, The yttrium-rich aluminum inner reaction zone includes one or more of the following: yttrium-aluminum oxide, yttrium-aluminum-silicon composite reaction phase, aluminum-rich glass phase, and fine alumina grains; The aluminum-silicon crystals in the outer reaction zone of the aluminum-silicon crystals include secondary mullite crystals formed or continuing to develop during the firing process. The secondary mullite crystals are distributed in one or more of the following morphologies: short rod-shaped, elliptical, dot-shaped, and needle-shaped.

6. A method for preparing a rare-earth modified high-strength porcelain insulator, characterized in that, Includes the following steps: The corundum skeleton particles are screened, washed, and dried. The corundum framework particles are coated with an inner layer precursor slurry containing yttrium and aluminum sources to form a yttrium-rich aluminum inner layer on the surface of the corundum framework particles. A corundum skeleton particles with a yttrium-rich aluminum inner layer are coated with an outer layer precursor slurry containing aluminum and silicon sources. An aluminum-silicon outer layer is formed on the outside of the yttrium-rich aluminum inner layer. Then, drying and pre-fixing treatment are performed to obtain double-layer coated corundum skeleton particles. The main ceramic material used to form the aluminosilicate continuous matrix is ​​separately wet ball-milled, and the double-layer coated corundum skeleton particles are not added during the wet ball milling of the main ceramic material; After the main ceramic material is wet ball milled, the double-layer coated corundum skeleton particles are added to the main ceramic material and mixed with low shear to obtain a mixed ceramic material. The mixed ceramic material is dehydrated, and the dehydrated mixed ceramic material is kneaded and aged or granulated according to the molding method. Then it is molded, dried and glazed to obtain an insulator blank. The insulator blank is heated to the peak firing temperature and held at that temperature to densify the insulator blank. After holding at the peak firing temperature, the insulator blank is cooled to an interface reaction temperature lower than the peak firing temperature, and then held at the interface reaction temperature. Subsequently, controlled cooling is performed to obtain the rare earth modified high-strength porcelain insulator. After firing, at least some of the corundum skeleton particles form a rare earth modified reaction transition structure between the fired aluminosilicate continuous matrix and the corundum skeleton particles. Along the direction of the corundum skeleton particles toward the aluminosilicate continuous matrix, the rare earth modified reaction transition structure sequentially includes a yttrium-rich aluminum inner reaction zone and an aluminum-silicon crystal outer reaction zone.

7. The preparation method according to claim 6, characterized in that, Based on a dry basis of 100 parts by weight, the main ceramic material comprises 32-45 parts of calcined bauxite, 18-28 parts of kaolin, 8-16 parts of plastic clay, 8-16 parts of feldspar, 3-9 parts of quartz, 6-16 parts of fine-grained alumina, and 0.3-2.0 parts of mineralized components, with the total amount of each component being 100 parts. The mineralized components include at least one of talc and dolomite; The amount of corundum skeleton particles added is 12 to 28 parts by weight relative to 100 parts by weight of the main ceramic material.

8. The preparation method according to claim 6, characterized in that, Based on 100 parts by weight of the corundum skeleton particles, the solid components in the inner layer precursor slurry include 2 to 8 parts of aluminum source converted to Al2O3, 0.4 to 2.4 parts of yttrium source converted to Y2O3, and 0.1 to 0.8 parts of film-forming agent. The yttrium source includes one or more of yttrium nitrate, yttrium acetate, yttrium carbonate dispersion, and yttrium oxide sol, and the aluminum source includes one or more of boehmite sol, alumina sol, nano alumina powder, and submicron alumina powder; Based on 100 parts by weight of the corundum skeleton particles, the solid components in the outer layer precursor slurry include 3-8 parts of metakaolin, 2-8 parts of fine alumina, 0-1.5 parts of silica sol solids, and 0.1-0.6 parts of film-forming agent or dispersant. The mass ratio of Al2O3 to SiO2 in the outer layer precursor slurry is 2.0 to 3.

2.

9. The preparation method according to claim 6, characterized in that, The pre-fixation treatment temperature of the double-layer coated corundum skeleton particles is 650-850℃, and the holding time is 30-120min. The slurry formed by wet ball milling of the main ceramic material has a D50 of 1.5–4.5 μm and a sieve residue of no more than 0.5% on a 45 μm sieve. After the double-layer coated corundum skeleton particles are added to the main ceramic material, they are mixed under low shear at a speed of 30-100 r / min for 5-20 min.

10. The preparation method according to claim 6, characterized in that, The peak firing temperature is 1260–1325°C, and the holding time at the peak firing temperature is 10–45 min. After holding at the peak firing temperature, the temperature is reduced to 1160-1220℃ at a rate of 1-4℃ / min, and held at 1160-1220℃ for 30-120min. After maintaining the temperature at the interface reaction temperature, cool the temperature to below 900℃ at a cooling rate of 2-5℃ / min, and then allow it to cool naturally.